2019
DOI: 10.1115/1.4043864
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Energy Conversion Enhancement Studies Using Low Concentration Nanofluids

Abstract: The present study aims to develop a compact experimental facility to trap solar energy. Line focusing concentrators, i.e., Fresnel lens and secondary reflectors, are coupled to enhance the photothermal conversion efficiency. Two types of receiver tubes are used, a plain copper tube and an evacuated glass tube embedded with a copper tube. Surfactant-free multiwalled carbon nanotubes–Therminol55 nanofluid with concentrations of 25, 50, 75, and 100 ppm are used in this study. The characterization of the nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…used Therminol55 /Al 2 O 3 nanofluids with Fresnel lens and evacuated tubes and obtained a maximum photo‐thermal conversion efficiency of 62.7% for .1% volume concentration. The photo‐thermal conversion efficiencies of plain copper tube and evacuated tubes were 12.65% and 17.36% for the concentration of 100 ppm (Therminol55/MWCNTs), reported by Kalidoss et al 13 . This clearly shows that the combination of evacuated tubes and nanofluids play a major role in solar thermal conversion.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…used Therminol55 /Al 2 O 3 nanofluids with Fresnel lens and evacuated tubes and obtained a maximum photo‐thermal conversion efficiency of 62.7% for .1% volume concentration. The photo‐thermal conversion efficiencies of plain copper tube and evacuated tubes were 12.65% and 17.36% for the concentration of 100 ppm (Therminol55/MWCNTs), reported by Kalidoss et al 13 . This clearly shows that the combination of evacuated tubes and nanofluids play a major role in solar thermal conversion.…”
Section: Resultssupporting
confidence: 62%
“…The absorbance and extinction coefficient trends of Al 2 O 3 nanofluids observed in this study are similar to that reported by various researchers. 13,20,39,40 The extinction results are derived from the absorbance results using mathematical equations. The maximum values obtained for Al 2 O 3 and CuO nanofluids, respectively, are 5.5 and 3.4 cm -1 in the UV region.…”
Section: Absorbancementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental efficiency of the ORC was 6.2%, and the power generated was 11.43 KWh/day. The optimum concentration for the optical absorbance of Therminol 55-MWCNTs was reported by Kalidoss et al [23].…”
Section: Introductionmentioning
confidence: 82%
“…The recorded temperature values at the specific time are added and divided by the number of days (five days each) for extracting the average values. The same procedure was followed in the research work of Kalidoss et al [23]. The experimental setup is placed in the surface azimuth angle 0°which is the true north-south direction.…”
Section: Description Of the Experimentsmentioning
confidence: 99%